Perancangan awal wind tunnel untuk pengujian turbin angin - Alexander Matthew; Levin Halim (Jurnal Teknik Mesin Indonesia, 2022)
As the supply of natural resources related to petroleum is dwindling, the step that can be taken is to switch to renewable energy sources that can minimize existing problems. Renewable energy sources themselves have several types, namely solar, water, and wind power. Which will be discussed further on the type of wind that is considered quite potential if developed in Indonesia. To be able to produce electrical energy from the wind, a Wind Turbine is also needed which is used as a supporting tool. The development of the Wind Turbine is still very necessary because the Wind Turbine itself needs to be adjusted to the conditions of placement and the conditions of the place that wants to use the Wind Turbine. In addition, to test the Wind Turbine itself is quite difficult because it depends on the uncertain natural conditions and the position of the placement of the Wind Turbine itself. For this reason, the Wind Tunnel can be used to support the research and development of the Wind Turbine. Wind Tunnel itself has several types that are tailored to the desired needs and needs. In this discussion, the Wind Tunnel discussed is a Subsonic type which has a Mach Number < 1. By using the Wind Tunnel itself, it is hoped that the research and analysis process of the Wind Turbine can be helped and it can be easier to find what things need to be developed. As a support for Wind Tunnel design, Solidworks software is also used which can be used to support the desired Wind Tunnel design process, because it can also be used to simulate.